Vision Impairment Science, art and lived experience - Crossland, Michael (UCL Press, 2024)
What is it like to go blind? 350 million people around the world live with severe vision impairment, ranging from those who can see a couple of letters on a sight chart to those who perceive no light at all. In this book we meet some of them, including artists, poets, scientists, architects, politicians, broadcasters and musicians. Together, we discuss every stage of life with vision impairment - from childhood and education to dating, employment and ageing - as well as the portrayal of blind people in literature and film, the use of technology by people with vision impairment, and the psychological effects of losing vision. Vision Impairment also reviews the major causes of sight loss today and shows the effect of these diseases on visual function. It surveys new and emerging treatments for serious eye diseases and explores what it is like to have vision restored after decades of being blind. Based on Michael Crossland's extensive work in children's and adults' low vision clinics, and his 20 years of research into vision impairment, the book blends individual stories, key research findings and the most recent scientific discoveries to present an informative yet optimistic overview of living with sight loss. Praise for Vision Impairment 'The key strength of this book is how scientific concepts around ophthalmology, vision science and sight loss are brought to life by letting patients explain what these concepts mean to them. This is not a book that has been written "about" patients; it has been written "with" them. In this sense, it is very much original, and I enjoyed reading it tremendously.' Keziah Latham, Anglia Ruskin University